The Effect Of Competency And Work Facilities On Employee Performance Of Regional Financial Agencies In The Government Of Seluma Regency - Hartati, Yeni; Susanti, Neri; Astuty, Kamelia (Fakultas Ekonomi Universitas Dehasen Bengkulu, 2025)
Employee performance is the result of job functions or activities of a person or group in an organization that is influenced by various factors to achieve organizational goals. To achieve this, requires competence and work facilities at the Regional Financial Agency in the Government of Seluma Regency that are selective. The purpose of this study is to determine the effect of competency and work facilities on employees performance of Regional Financial Agency in the Government of Seluma Regency. The research method used is quantitative, the data collection technique in this study is a questionnaire technique, with a research sample of 63 respondents. The results showed that multiple linear regression Y =22,275 + 0.134 X1 + 0.446 X2 + 3,257. Where the coefficient is positive, it means that there is a positive or unidirectional relationship between the competency variable (X1) and work facilities, on employee performance at the Regional Financial Agency in the Government of Seluma Regency. The results show that the competency test results (XI) show t count 3.060> t table 1.670 and sigfinication 0.003 <0.05, then the results of the hypothesis Ha is accepted and Ho is rejected, meaning that competency (XI) has a positive and significant effect on employee performance at the Regional Financial Agency in the Government of Seluma Regency. This means that the hypothesis is accepted. The test results for work facilities (X2) show t count 7,227>t table 1,670 and sigfinication 0.000 <0.05, then the results of the hypothesis Ha is accepted and Ho is rejected, meaning that work facilities (X2) have a positive and significant effect on employee performance at the Regional Financial Agency in the Government of Seluma Regency. This means that the hypothesis is accepted. So, the suitability of employee facilities can speed up one's work. The results of the comparison value of the value of Fcount with Ftable, Fcount is greater than Ftable, namely 29.873> 2.76, it is concluded that Accepting the Hypothesis, meaning that there is a simultaneous influence between competency (XI) and work facilities (X2) on employee performance (Y) at the Regional Financial Agency in the Government of Seluma Regency. This can be seen at a significance level of 0.000 <0.05.